2009
DOI: 10.2175/193864709793954178
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nitrification Kinetics for a 2.0 MGD IFAS Process Demonstration

Abstract: The James River Treatment Plant (JRTP) operated a 2 MGD Integrated Fixed Film Activated Sludge (IFAS) demonstration process from November 2007 to April 2009 to explore IFAS performance and investigate IFAS technology as an option for a full scale plant upgrade in response to stricter nutrient discharge limits in the James River Basin. During the study, nitrification kinetics for both ammonia and nitrite oxidizing bacteria and plastic biofilm carrier biomass content were monitored on a near-weekly basis compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2011
2011
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
0
0
2
Order By: Relevance
“…The recorded kinetics of this study demonstrated the ability of attached growth nitrifiers to maintain significant kinetics after various lengths of exposure times to cold temperatures. These findings have been supported in recent studies on integrated fixed film activated sludge treatment plants, where the attached growth nitrifiers demonstrated higher levels of activity during exposures to cold temperatures (Bott, 2010;Thomas et al, 2009). Rates of nitritification and nitratification were comparable at 20 uC and CGA TCC CCT GCT TTT CTC C Ammonia-oxidizing bacteria of Proteobacteria Cy3 55 0.020 (Mobarry et al, 1996) NIT3 CCT GTG CTC CAT GCT CCG Nitrobacter spp.…”
Section: Resultssupporting
confidence: 56%
“…The recorded kinetics of this study demonstrated the ability of attached growth nitrifiers to maintain significant kinetics after various lengths of exposure times to cold temperatures. These findings have been supported in recent studies on integrated fixed film activated sludge treatment plants, where the attached growth nitrifiers demonstrated higher levels of activity during exposures to cold temperatures (Bott, 2010;Thomas et al, 2009). Rates of nitritification and nitratification were comparable at 20 uC and CGA TCC CCT GCT TTT CTC C Ammonia-oxidizing bacteria of Proteobacteria Cy3 55 0.020 (Mobarry et al, 1996) NIT3 CCT GTG CTC CAT GCT CCG Nitrobacter spp.…”
Section: Resultssupporting
confidence: 56%
“…(Macquarrie 2009) estudió la actividad nitrificante de la biomasa en suspensión y de la biomasa en la biopelícula basándose en los datos proporcionados por (Thomas et al 2009). Los resultados de este estudio indican que la actividad nitrificante, medida como mg N-NH4/g SS/h), es mayor en la biopelícula que en la biomasa en suspensión:…”
Section: A) Nitrificaciónunclassified
“…Ilustración VI-68 -Efecto de la variación de la concentración de oxígno sobre la velociddad nitrificación en la biopelícula en un sistema IFAS (Thomas et al 2009). …”
Section: A) Nitrificaciónunclassified